MORPHOLOGICAL FEATURES OF MESENTERIAL LYMPH NODES IN EXPERIMENTAL HYPOTHYROIDIS IN THE MOTHER - Feruza Kh. Azizova; Mokhizoda A. Mirtolipova (Central Asian Journal of Medicine, 2023)
According to statistics, half of the world’s population has health problems related to the thyroid gland. The effect of experimental hypothyroidism in female rats on the development, formation and growth of mesenteric lymph nodes (MLN) of the offspring was studied. Hypothyroidism in female rats was induced by oral administration of the antithyroid drug Mercazolil at a dose of 0.5 mg per 100 g of body weight for 21 days. After establishing a stable decrease in the concentration of free thyroxine in the blood serum, the females were fertilized by healthy males. During pregnancy and lactation, females continued to be administered a maintenance dose of the drug. At 3, 7, 14, 21 and 30 days after birth, the development and formation of MLN offspring obtained from females with experimental hypothyroidism were morphologically studied. It has been established that in offspring born under conditions of maternal hypothyroidism, the time parameters for the formation of structural and functional zones of MLN, especially its T-dependent zones, significantly lag behind the control.